Role of Information and Communication Technology (ICT) in Development of Higher Education in India: Enhancing Higher Education in India through Information and Communication Technology (ICT) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The modern learning paradigm of constructivism is greatly aided by the use of ICT intoeducational settings. Integrative technology that promotes greater use of ICT in teaching has beenshown to have a beneficial effect on students' academic outcomes. The study used a descriptiveresearch approach to look at the connection between ICT and progress in higher education. This study isan effort highlight the government policiesinitiatives to enhance higher education among all eligible andinterested persons of India and to bring focus on execution of policies concerning the integration of ICTand the efficiency of the classroom. It is firmly highlighted that use of technology should increase onlineand interactive education opportunities for all students. Teachers can do their jobs well with the ongoingeducation and development. The educational environment as well as administrative system in highereducation sector of India can be more efficient, transparent and inclusive through introduction and wideuses of ICT.